(untitled) (Jurnal Bahasa, 2002)
It is shown that etymologically the Malay words for numbers are based on position of fingers on one hand. We then argue that linguistically, and we believe that this is the first time ever, there is a strong evidence that the Malay number system is a quinary or denary/decimal system. To establish this fact we found new possible origin of the Malay words for empat, enam and puluh. Then we also obtain a Malay numeral system based on fingers and we believe that this is the first proposal of its kind. This shows that there is a strong possibility that fingers had been used to signify numbers in the Malay world just like the European before their complete adoption of the Muslim (Arabic) numeral in the 17th century, and presently the use of fingers in the whole world among people in the stock exchange business. Even though the Malay number is a quinary or denary system we find that the Malay concept of measurement is based on four, a quartenary system. This is to be compared with the British concept of measurement which is based twelve (duodenary!duodecimal) whereas their system of numbers is denary. Reasons for the Malays to adopt a quarternary system of measurement are also discussed. Meanwhile there was a unique lslamic Malay calendar of eight-year cycle (still consistent with the quarternary system of numbers) known as daur kecil among non-Javanese and windu among the Javanese used together with the Islamic calendar since 16th century with four variations due to different adoption of Arabic alphabets, namely Acheh-Wilkinson, Aceh-al-Attas, Campa and Javanese versions.